Dampak Pembangunan Kawasan Minapolitan Terhadap Desa Warsawa Di Kabupaten Kuantan Singingi - Astuti, Puji (IPTEKIN Jurnal Kebijakan Pembangunan dan Inovasi, 2023)
The Minapolitan approach is a breakthrough in rural development programs on rural development itself. In Kuantan Singingi Regency, Riau Province, a location for the development of freshwater aquaculture is called the minapolitan, through the Decree of the Regent of Kuantan Singingi Number 156 of 2008 concerning the Determination of the Location for the Development of the Minapolitan Area of Kuantan Singingi Regency, the one of Minapolitan area is Marsawa Village, Sentajo Raya District. This study aims to identification about the impact of the minapolitan development program in Marsawa Village, namely economic, social, environmental, and infrastructure impacts. This study uses qualitative and quantitative research methods. The data was collected through observation, questionnaires, and interviews. Questionnaires were given to fish cultivators and analyzed through percentages of respondents and interviews with officials and community leaders. The results of this study concluded that the impact of minapolitan development in rural areas is; (1) Increasing family income which affects its economic value, accelerating economic changes in rural areas, creating job references, increasing people's safety, increasing market potential, increasing the value of regional productivity, encouraging minapolitan production, increasing the possibility of marketing it in fish cultivators; (2) Increasing the number of counseling and technical guidance on fisheries, increasing social activities, adding value to social issues, encouraging community enthusiasm about aquaculture, improving nutrition, health issues, and increasing trade union activities; (3) environmental cleanliness, fresh, healthy and neat; (4) Improving the quality of irrigation and sanitation facilities, improving workplaces and networks, and increasing the availability of clean water.